BIOSINTESIS NANOPARTIKEL PERAK MENGGUNAKAN EKSTRAK EMPELUR BATANG SAGU BARUK (ARENGA MICROCARPHA) DAN AKTIVITAS ANTIOKSIDANNYA - Tapa, Fitriyanti La; Suryanto, Edi; Momuat, Lidya Irma (Sam Ratulangi University, 2016)
Objectives of this research to synthesize silver nanoparticles with extract pith of sago baruk (Arenga microcarpha) by using temperature variations and study the antioxidant activity of silver nanoparticles. Synthesis of silver nanoparticles using green methods